2019
DOI: 10.1186/s12920-019-0521-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential biomarkers for diagnosis of pancreatic and biliary tract cancers by sequencing of serum microRNAs

Abstract: Background Pancreatic and biliary tract cancer (PC and BTC, respectively) are difficult to diagnose because of their clinical characteristics; however, recent studies suggest that serum microRNAs (miRNAs) might be the key to developing more efficient diagnostic methods for these cancers. Methods We analysed the genome-wide expression of serum miRNAs in PC and BTC patients to identify novel biomarker candidates using high-throughput sequencing and experimentally validate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 58 publications
2
20
0
Order By: Relevance
“…For example, miR-128 and miR-409 are significantly downregulated, while miR-21 and miR-200 are obviously overexpressed. [38][39][40] Notably, the overexpression trend of miR-21 was consistent with the results in our study. We also found that single miR-21 alone could distinguish the malignant group from the control group and the benign group from the control group but could not distinguish the malignant group from the benign group.…”
Section: Discussionsupporting
confidence: 92%
“…For example, miR-128 and miR-409 are significantly downregulated, while miR-21 and miR-200 are obviously overexpressed. [38][39][40] Notably, the overexpression trend of miR-21 was consistent with the results in our study. We also found that single miR-21 alone could distinguish the malignant group from the control group and the benign group from the control group but could not distinguish the malignant group from the benign group.…”
Section: Discussionsupporting
confidence: 92%
“…Overexpression of miR-744-5p induced apoptosis of ovarian cancer cells and high miR-744-5p expression was associated with prolonged disease-free survival of patients with ovarian cancer ( 19 ). Additionally, the serum level of miR-744-5p was dysregulated in various types of cancers, such as pancreatic and biliary tract cancers, which indicates the potential significance of miR-744-5p in the diagnosis of cancers ( 21 ). A recent study also reported decreased expression of miR-744-5p in NSCLC ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study also demonstrated that miR-361 promoted the sensitivity of CRC cells to 5-fluorouracil, indicating miR-361 as a possible drug target to suppress tumorigenesis (18). Notably, recent studies revealed the significantly dysregulated expression of miR-744-5p in multiple cancers, such as hepatocellular carcinoma, gastric cancer and pancreatic cancer (19)(20)(21). Dysfunction of miR-744-5p has been suggested to play suppressive roles in the development of cancers.…”
Section: Introductionmentioning
confidence: 99%
“…miR-744-5p is differentially expressed in various cancers and is involved in tumor progression. [12][13][14] Studies have indicated that miR-744-5p is lowly expressed in multiple cancers, like colorectal cancer, cervical cancer and glioblastoma, and overexpression of miR-744-5p can inhibit cell proliferation, migration, and invasion. [15][16][17] Moreover, miR-744-5p is also down-regulated in EOC cells, its upregulation could induce cell apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…And miRNAs as oncogene or anti‐oncogene have attracted more and more researchers' attention. miR‐744‐5p is differentially expressed in various cancers and is involved in tumor progression 12–14 . Studies have indicated that miR‐744‐5p is lowly expressed in multiple cancers, like colorectal cancer, cervical cancer and glioblastoma, and overexpression of miR‐744‐5p can inhibit cell proliferation, migration, and invasion 15–17 .…”
Section: Introductionmentioning
confidence: 99%